Pengaruh Penggunaan Perangkat Digital Terhadap Timbulnya Nyeri Leher dan Bahu Pada Mahasiswa Fakultas Kedokteran Universitas Yarsi - anastasya sabrina attawuni (Junior Medical Journal, 2022)
Background: The use of digital devices such as Personal Computers, laptops, smartphones that do not pay attention to the duration and ergonomic position will cause musculoskeletal pain such as in the neck and shoulders. Objective: To determine the effect of posture and duration of using the device on the incidence of neck pain in students of the Faculty of Medicine, University of Yarsi. Research Method: Analytical research with a cross sectional approach. The population and sample are all YARSI University Medical Faculty students class of 2020. The type of data is primary data using a questionnaire. Data analysis was performed using univariate and bivariate. Research Results: Obtained 140 respondents met the inclusion criteria. Based on the duration of use of the device (users), it is found very often 38.6%; often 29.3% ; being 27.9% and 4.3% rare. The posture of 72.9% of users is sitting reclined; 23.6% sat without back support; 3.6% lying down. Complaints of pain in the user's upper neck, 14.3% did not complain, 40% had moderate pain, 33.6% had pain, and 7.9% had very much pain. For complaints of lower neck pain, 12.1% did not complain, 47.1% had moderate pain, 33.6% had pain and 7.1% had very much pain. Complaints of shoulder pain, as much as 10.7% did not complain, 40% had some pain, 38.6% had pain, and 10.7% had very much pain. Most of the respondents experienced one-sided shoulder pain 61.4%. In the user posture group, the incidence of upper and lower neck pain, as well as the shoulders, was analyzed using the non-parametric Kruskal-Wallis test, and all results showed a p value above 0.05. To find out the difference between the duration and the onset of upper neck pain, a test was performed. post-hoc, and in the comparison of the